The Tensile Strength of Full-Thickness Skin: A Laboratory Study Prior to Its Use as Reinforcement in Parastomal Hernia Repair - Holmdahl, Viktor; Backman, Olof; Gunnarsson, Ulf; Strigård, Karin (Frontiers in Surgery, 2019)
Purpose. Parastomal hernia is a common complication of an enterostoma. Current methods of repair have high recurrence rates and are associated with severe complications. Autologous full-thickness skin as reinforcement may reduce the recurrence and complication rates. This study aims to investigates the tensile strength of full-thickness skin; information that is essential if we are to proceed with clinical trials on humans. Methods. Full-thickness skin samples from 12 donors were tested for tensile strength, as well as the load tolerated by a suture through the skin. Strips of skin were cut out and stretched until breaking point. Sutures were made through skin samples and traction applied until either the tissue or the suture gave way. All done while recording the forces applied using a dynamometer. Identical tests were carried out on commercially available synthetic and biologic graft material for comparison. Results. The full-thickness skin strips had a median tensile strength of 604N/cm. This tensile strength was significantly higher than that of the compared materials evaluated in this study. In full-thickness skin, the suture or tissue endured a median force of 67N before giving way, which was as high as or higher than similar sutures through the compared materials. Conclusions. The tensile strength of full-thickness skin vastly exceeds the physiological forces affecting the abdominal wall, and sutures through skin endure high loads before giving way. The tensile strength of a full-thickness skin graft and the strength of sutures through this material will not limit its use for reinforcement in parastomal hernia repair.